Residual load bearing capacity and failure mechanism of impacted high-strength reinforced concrete shear beams. (March 2021) - Dok, Gokhan; Caglar, Naci; Ilki, Alper; Yilmaz, Cemal
Highlights: Studies on the post-impact behavior of RC members are very limited. The effects of impact loading on the residual shear capacity of RC beams are disclosed. Shear strength, stiffness, and energy dissipation characteristics are studied after impact damage. Dynamic increase factor for impact behavior is presented. Abstract: An experimental study was performed to determine the dynamic structural response of high-strength reinforced concrete (RC) beams exposed to impacts of various energies. The residual load-bearing capacities of the impacted beams were measured by static loading tests after their dynamic impact responses had been assessed. Considering the shear behavior of the RC beams, their cross-sectional dimensions and length of were set as 250 mm × 400 mm and 2800 mm, respectively. Dropping masses of 240, 360, and 480 kg from a height of 3 m were used in the impact tests. The dynamic strength, acceleration, and deformation mode depending on the effect of the impact were investigated. After the impact tests, quasi-static bending tests of the impact-damaged beams were performed, and the results were compared with those of an undamaged reference RC beam. The residual strength, stiffness and the failure mechanism were selected as comparison criteria to evaluate the experimental results of the static tests. The dynamic test results depended on the applied impact energy and the damage intensity of the specimens. The residual strength and stiffness of the impact-damaged beams were lower than those of the reference specimen, particularly for the beam subjected to the largest impact. In addition, a significant reduction in energy dissipation capacity of the impact-damaged beams was observed during the static tests.